Assessment of National Automotive Design and Development Council Training Programmes in Informal Sector Automobile Mechanics in Nigeria - Anietie Effiong; I. Y. Shehu; S. M. Yalams; Abdulgafar Ahmed (Ilmu Inovasi Nusantara, 2023)
The purpose of this study was to assess the NADDC training programme for the informal sector of automobile mechanics in Nigeria. Three research questions guided the study. The design of the study was a descriptive survey design. The population of the study was one thousand, two hundred and two respondents (1,202). The study covered the entire country of Nigeria, which is divided into 6 geopolitical zones comprising of 15 training centres. The sample for the study was two hundred and seventy-two respondents, which was purposefully selected. The instrument for data collection was a structured questionnaire developed by the researcher. The collected data was analysed using mean and standard deviation, and hypotheses were tested using the t-test and ANOVA. The result revealed that the fifteen (15) objectives are highly appropriate for the training of automobile mechanics in the informal sector on maintenance and repairs of vehicles in Nigeria. Human resources at the training centres are highly adequate for the implementation of NADDC training programmes for automobile mechanics in the informal sector on maintenance and repairs of vehicles in Nigeria. One of the suggestions was that a workshop be set up to teach the trainers how to use the materials given, since most machines, tools, or instruments are very computerized. NADDC training programme graduates should be closely monitored for further training and retraining to meet the challenge of modern technologies and innovations in automobiles